2019
DOI: 10.1155/2019/4619865
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Enhances Apoptotic and Oxidant Effects of Paclitaxel through TRPM2 Channel Activation in DBTRG Glioblastoma Cells

Abstract: Numerous studies have reported a strong association between increased production of reactive oxygen species (ROS) and the pathobiology of several diseases, and cancer in particular. Therefore, manipulation of cellular oxidative stress levels represents an important therapeutic target. Recently, resveratrol (RESV), a naturally occurring phytochemical, has been shown to sensitize several cell lines to the anticancer effects of other chemotherapeutic agents, including paclitaxel (PAX). However, the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 84 publications
2
37
0
Order By: Relevance
“…However, we observed decrease of rGSH level and GPx activity in the SH-SY5Y cells exposed to HYPX, which were upregulated by the RSV treatment. These data are agreement with previous results showing decreased oxidation of thiol redox system members in the SH-SY5Y cells after RSV treatment, providing evidence for a protective effect of RSV through upregulation of rGSH and GPx in diminishing neuronal oxidative stress and inflammation during HYPX 3,24 . The observed decreases in ROS and MDA upon exposure of HYPX may therefore be due to the increase repair of respiratory chain enzyme complex activity through upregulation of rGSH and GPx redox system in the mitochondria of SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, we observed decrease of rGSH level and GPx activity in the SH-SY5Y cells exposed to HYPX, which were upregulated by the RSV treatment. These data are agreement with previous results showing decreased oxidation of thiol redox system members in the SH-SY5Y cells after RSV treatment, providing evidence for a protective effect of RSV through upregulation of rGSH and GPx in diminishing neuronal oxidative stress and inflammation during HYPX 3,24 . The observed decreases in ROS and MDA upon exposure of HYPX may therefore be due to the increase repair of respiratory chain enzyme complex activity through upregulation of rGSH and GPx redox system in the mitochondria of SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed modulation of the TRPM2 channel via inhibition excessive ROS generation and increase of thiol redox cycle antioxidants (rGSH and GPx) in the HYPX-induced SH-SY5Y cell by the RSV and TRPM2 channel blocker (ACA and 2-APB) treatments. Similarly, we recently observed a modulator action of RSV on the TRPM2 channel activity in the DBTRG glioblastoma cells 24 .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations